Development and testing of the effectiveness of the guided discovery learning model: A strategy for accelerating student learning outcomes in science and biology - Ulfiana Djunaid; Fendrawaty Hilamuhu; Aswan Bannang (Journal of Environment and Sustainability Education, 2026)
This study aimed to develop and evaluate the effectiveness of a Guided Discovery Learning (GDL) model for teaching Protista material in junior high school biology. The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate), with the Develop phase integrating a quasi-experimental pretest–posttest control group design. A total of 60 eighth-grade students were selected through purposive random sampling and assigned to an experimental group (GDL) and a control group (conventional instruction). Data were collected using achievement tests, motivation questionnaires, and classroom observation sheets. Quantitative data were analyzed using t-tests, while effect sizes were calculated using Cohen’s d to determine the magnitude of instructional impact. The results showed that both groups demonstrated significant learning gains; however, the experimental group achieved substantially higher posttest scores (M = 78.4) and learning gains (ΔM = 32.8) compared to the control group (M = 55.3; ΔM = 11.1). Effect size analysis revealed a very large effect for the GDL model (d = 2.81), indicating strong educational significance. In addition, 85% of students in the experimental group reported high learning motivation, and 75% demonstrated active engagement during learning activities, exceeding those in the control group. These findings indicate that the Guided Discovery Learning model is highly effective in improving cognitive learning outcomes, motivation, and student engagement in biology learning. The study provides empirical support for constructivist and discovery-based instructional approaches and highlights the potential of GDL as a high impact pedagogical model for teaching complex biological concepts at the junior high school level.